2020
DOI: 10.2147/jpr.s233905
|View full text |Cite
|
Sign up to set email alerts
|

<p>Intrathecal Morphine Infusion Therapy via a Percutaneous Port for Refractory Cancer Pain in China: An Efficacy, Safety and Cost Utilization Analysis</p>

Abstract: Purpose: Intrathecal morphine infusion therapy via a percutaneous port (IMITPP) has been used widely for its relatively low initial cost. However, there is scarce knowledge about IMITPP. In this study, we sought to evaluate efficacy, complications, and the interval required to achieve the cost equivalence of IMITPP in patients with refractory cancer pain in China. Patients and Methods: A retrospective chart review was conducted on cancer patients who had received IMITPP at our hospital between April 2017 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 26 publications
7
20
0
Order By: Relevance
“…The disadvantage of ITT via an external pump is that patients must wear an external drug infusion pump and receive meticulous injection site care such as daily injection site disinfection, change of the butterfly‐winged needle in each visit, and avoiding inadvertent catheter dislodgement or removal in daily life, which could impair the performance of daily activity and further influence life satisfaction and affective experience (Bhatia et al., 2013 ; De Andres et al., 2020 ). The present study shows that ITT via the external system had a trend to decrease patients’ KPS scores, which is in accordance with a previous study and further proves the disadvantage of ITT via the external system (Qin et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The disadvantage of ITT via an external pump is that patients must wear an external drug infusion pump and receive meticulous injection site care such as daily injection site disinfection, change of the butterfly‐winged needle in each visit, and avoiding inadvertent catheter dislodgement or removal in daily life, which could impair the performance of daily activity and further influence life satisfaction and affective experience (Bhatia et al., 2013 ; De Andres et al., 2020 ). The present study shows that ITT via the external system had a trend to decrease patients’ KPS scores, which is in accordance with a previous study and further proves the disadvantage of ITT via the external system (Qin et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the incidence of infection is very low in the external group and shows no significant difference as compared to the implanted group. This profits partly from the utilization of the subcutaneous port that avoids a direct connection between the external infusion system and the intrathecal space There is no significant difference in the incidences of adverse events between the external and implanted groups an interval of 2 weeks, care transitions in the long-term ITT, and the careful prevention measures in daily life (Qin et al, 2020). The most frequent surgical complication was post-dural puncture headache in both groups, which suggests no significant difference in the risk of pericatheter CSF leakage between the two ITT systems (Adler & Lotz, 2017;Peralta et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In practice, many studies have revealed the significant effects of IMP on pain relief (8,(14)(15)(16). Meanwhile, IMP was reported to induce the improvement of physical status, like the results in our study (17). Psychological status is a research focus as well.…”
Section: Discussionsupporting
confidence: 75%
“…High cost limited the use of the implanted intrathecal morphine pump despite it is more suitable for longterm use. Recently, intrathecal morphine infusion therapy via a percutaneous port (IMITPP) has become a popular option for refractory cancer pain in some countries for its relatively lower cost [19]. In the present study, we assessed the e cacy and safety of IMITPP.…”
Section: Discussionmentioning
confidence: 98%
“…Due to its relatively lower cost, Intrathecal morphine infusion therapy via percutaneous port (IMITPP) may be a better option for cancer patients with a shorter predicted survival than via an implantable morphine pump [18,19]. IMITPP is a percutaneous port attached to an external drug infusion pump that allows for continuous intrathecal analgesia for the management of spontaneous resting pain (SRP), patientcontrolled intrathecal analgesia (PCIA) for the management of movement evoked breakthrough pain (MEBTP) and/or self-titrate to analgesic effect [16,20].…”
Section: Introductionmentioning
confidence: 99%